2022
DOI: 10.1186/s13063-022-06184-1
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Evaluation of Surgery in Elderly with Traumatic Acute SubDural Hematoma (RESET-ASDH trial): study protocol for a pragmatic randomized controlled trial with multicenter parallel group design

Abstract: Background The rapidly increasing number of elderly (≥ 65 years old) with TBI is accompanied by substantial medical and economic consequences. An ASDH is the most common injury in elderly with TBI and the surgical versus conservative treatment of this patient group remains an important clinical dilemma. Current BTF guidelines are not based on high-quality evidence and compliance is low, allowing for large international treatment variation. The RESET-ASDH trial is an international multicenter RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…However, survival and good functional outcome remain poor in many elderly patients, despite an aggressive treatment [ 14 , 15 , 16 , 17 ]. Therefore, in this age range, the treatment of choice is still debated and the object of ongoing trials [ 6 , 7 ], and most neurosurgeons prefer an initial conservative treatment, opting for surgery only in the case of an impaired state of consciousness. Although, while surgery has also been shown to have a major life-saving role in these patients when presenting with a severe clinical status, several studies have reported a high rate of poor functional outcome both at discharge and at 6 months follow-up, often due to the higher incidence of perioperative complications [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, survival and good functional outcome remain poor in many elderly patients, despite an aggressive treatment [ 14 , 15 , 16 , 17 ]. Therefore, in this age range, the treatment of choice is still debated and the object of ongoing trials [ 6 , 7 ], and most neurosurgeons prefer an initial conservative treatment, opting for surgery only in the case of an impaired state of consciousness. Although, while surgery has also been shown to have a major life-saving role in these patients when presenting with a severe clinical status, several studies have reported a high rate of poor functional outcome both at discharge and at 6 months follow-up, often due to the higher incidence of perioperative complications [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mean presenting GCS in these delayed surgery patients was rather low (12.4 ± 3.5) compared to what was expected in ASDH cases undergoing surgery. This is probably due to the awareness of the intrinsic high risk of this surgery in elderly patients [ 8 , 17 , 29 , 30 , 31 ], thus reflecting the current uncertainty of the best initial treatment in these patients [ 7 ]. Furthermore, this reflects the tendency of most neurosurgeons to choose to delay a possible craniotomy in elderly patients who do not show an initial serious clinical condition in the hope of a secondary chronicization of the hematoma, opening the possibility of its evacuation with a minimally invasive technique [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute subdural hematomas are intracranial hemorrhage that mortality and morbidity. 4,5 In the pathogenesis of chronic subdural hematoma, it is generally accepted that slowprogressing extra-axial hemorrhage occurs due to rupture of the bridging veins due to cerebral atopy. 6,7 The clinical findings show slow progression with the slow course of bleeding in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…For each patient, we retrieved the age, sex, Charlson Comorbidity Index (CCI), history of arterial hypertension, use of antithrombotic drugs, the need for an urgent coagulopathy correction at A&E admission, mechanism of injury, neurological status measured by the Glasgow Coma Scale (GCS) at admission and during the entire preoperative period, pupillary size and light reaction, neurological deficits, and seizures. Patients were divided in three GCS level groups, both at arrival and soon before surgery: mild (13)(14)(15), moderate (9)(10)(11)(12), and severe (3)(4)(5)(6)(7)(8).…”
Section: Clinical and Radiological Data Collectionmentioning
confidence: 99%